Aplikasi Penerapan TOPSIS Dalam Menentukan Kualitas Bibit Jambu Madu - Fahlevi, Muhammad Reza; Dwiki Putri, Dini Ridha (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Honey guava is guava that has an extraordinarily sweet taste. The level of sweetness of honey guava can beat the sweetness of apples and other fruits. Quality seeds are the main thing to get planting that can provide optimal results. Quality seeds come from pure varieties, free from pests, diseases, and treatments suitable for this type of honey guava. This application can help farmers to obtain information on determining the best quality of honey guava seeds by applying the TOPSIS method and can be better selected based on the specified criteria. The application of the TOPSIS method uses the PHP programming language and MySQL database, which states that the best alternative is the alternative that has the shortest distance from the positive ideal solution and the farthest distance from the negative ideal solution, so the best alternative is the alternative that has the largest percentage, namely Green Deli guava. With a value of 77.97%.